Risk factors and symptoms of cardiovascular disease in patients with different psychosocial features - Tadinac, Meri (Array, 2006)
In a group of cardiovascular patients who survived myocardial infarct we tested whether the presence of certain risk factors for another infarct (such as hypertension, high levels of cholesterol, triglycerides and blood glucose, and overweight) as well as other symptoms of cardiovascular system dysfunction (such as arrhythmias, hypotension, blood circulation problems and angina pectoris) differed among patients with different levels of anxiety, depression, and perceived social support. We found that patients with high level of anxiety and depression, and low level of perceived social support have (a) higher incidence of some risk factors (hypertension, overweight, high cholesterol and triglycerides, but not blood glucose) ; and (b) higher incidence of arrhythmias (and marginally heightened incidence of hypotension, but not other cardiovascular disturbances), compared to patients with lower level of anxiety and depression and higher level of perceived social support. The results are interpreted in the framework of the biopsychosocial model of illness.